2018
DOI: 10.1111/1462-2920.14238
|View full text |Cite
|
Sign up to set email alerts
|

Community and functional shifts in ammonia oxidizers across terrestrial and marine (soil/sediment) boundaries in two coastal Bay ecosystems

Abstract: Terrestrial-marine boundaries are significant sites of biogeochemical activity with delineated gradients from land to sea. While niche differentiation of ammonia-oxidizing archaea (AOA) and bacteria (AOB) driven by pH and nitrogen is well known, the patterns and environmental drivers of AOA and AOB community structure and activity across soil-sediment boundaries have not yet been determined. In this study, nitrification potential rate, community composition and transcriptional activity of AOA and AOB in soil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 81 publications
3
33
0
Order By: Relevance
“…The dominance of the AOB community by Nitrospira in the present study is consistent with many studies of AOB communities in terrestrial ecosystems ( Figure S2) (Shen et al, 2011;Xiao et al, 2014). The soil pH was neutral in the experimental soils, ranging from 7.12 to 7.37 (Table S1), providing a suitable soil environment for Nitrosopira, especially Nitrosopira cluster 3 (Stephen et al, 1996;Zhang et al, 2018). In addition, the soil NH 4 + content of N-treatments was significantly improved compared to the control treatment, differing from 3.33 mg kg −1 (N0P0) to 28.07 mg kg −1 (N2P3), providing more energy for NH 3 oxidization (Table S1).…”
Section: Integrated Responses Of Ammoniaoxidizer-soil-plant Systemssupporting
confidence: 90%
See 1 more Smart Citation
“…The dominance of the AOB community by Nitrospira in the present study is consistent with many studies of AOB communities in terrestrial ecosystems ( Figure S2) (Shen et al, 2011;Xiao et al, 2014). The soil pH was neutral in the experimental soils, ranging from 7.12 to 7.37 (Table S1), providing a suitable soil environment for Nitrosopira, especially Nitrosopira cluster 3 (Stephen et al, 1996;Zhang et al, 2018). In addition, the soil NH 4 + content of N-treatments was significantly improved compared to the control treatment, differing from 3.33 mg kg −1 (N0P0) to 28.07 mg kg −1 (N2P3), providing more energy for NH 3 oxidization (Table S1).…”
Section: Integrated Responses Of Ammoniaoxidizer-soil-plant Systemssupporting
confidence: 90%
“…Our findings showed that pH was an important edaphic factor constructing the AOB community (Figure 3). In the soil/sediment interface and in the sediments of two coastal bays, Zhang et al (2018) also found that pH was the key factor determining the abundance of AOB and Nitrosopira preferred in neutral soils surroundings. Taken together, the fact that Nitrosopira were dominant highlighted that neutral pH and higher NH 4 + concentrations promoted the activity of AOB in this steppe grassland.…”
Section: Integrated Responses Of Ammoniaoxidizer-soil-plant Systemsmentioning
confidence: 86%
“…Surface mud samples (0 to 2 cm) were collected on 11 January 2017 from Rusheen Bay, Ireland (53.2589° N, 9.1203° W) (presence of amoA genes/transcripts previously established (Duff et al ., ; Zhang et al ., ) in sterile 50 ml Eppendorf tubes, flash frozen and stored at −80°C until subsequent use.…”
Section: Methodsmentioning
confidence: 99%
“…Surface mud samples (0 to 2 cm) were collected on 11/01/2017 from Rusheen Bay, Ireland (53.2589° N, 9.1203° W) (presence of amoA genes/transcripts previously established [30, 31] in sterile 50ml Eppendorf tubes, flash frozen and stored at -80°C until subsequent use.…”
Section: Methodsmentioning
confidence: 99%